The gateway to the castle in Wales (1934)
Caption reads: 'The gateway to the castle in Wales. Buster and Lorna'. Likely Buster Collier and Lorna Velie Hearst (married at the time to George Randolph Hearst, Jr.), who visited St. Donat's with Hearst in 1934.